Estratégias para redução da produção de acetato em cultivos de Salmonella typhimurium - Fuzer Neto, José Roberto (2017)
In recent years, the application of attenuated Salmonella spp. has been investigated for development of several biotechnological products, mainly vaccines. However, the implementation of industrial processes to obtain these products depends on the development of strategies for this microorganism high-cell density cultures (HCDC). One of the HCDC’s greatest challenges is overcoming Salmonella’s metabolic limitations, as it presents a high organic acids production (mainly acetic acid) that inhibits biomass formation. In this context, this work proposes two approaches to deal with this problem and implement Salmonella’s HCDC: studying the cultivation of S. typhimurium using glycerol as carbon source to reduce the generation of organic acids; studying the cultivation of a recombinant strain of S. typhimurium expressing the enzyme acetyl-CoA synthetase (ACS) from E. coli, for improved acetate assimilation). Initially, cultures were grown in agitated flasks in minimal media for two carbon sources (glucose or glycerol) for the wild-type and the recombinant strain. After the preliminary experiments, the recombinant strain was cultivated in bioreactor operated in batch mode with minimal medium formulated with glycerol, glucose or acetic acid as carbon source, to evaluate acetate production and assimilation. The wild-type strain was cultivated in a continuous-mode bioreactor on minimal medium with glycerol at D=0.10; 0.17 and 0.22 h-1 to evaluate the S. typhimurium glycerol metabolism. During the cultivations, samples were collected and analyzed by high-performance liquid chromatography to quantify the production of organic acids and substrate consumption. To quantify the concentration of biomass, optical density (600 nm) readings of culture broth and dry cell weight measurements were performed. Agitated flasks and batch cultivations results indicated that the acetate production is reduced in medium with glycerol for both strains, and that the genetically modified cells present a lower acetate accumulation phenotype compared to the wild-type. Continuous cultures of the wild-type strain showed no acetate accumulation for a 0.1 h-1 dilution rate. At rates of 0.17 h-1 and 0.22 h-1 acetate accumulation was observed, but acetate flux was 2-fold lower than the flux reached in chemostat with glucose-formulated medium. Simulations were performed with the STM_v1.0 model using as input data the glycerol and oxygen fluxes estimated from the experimental results. Good predictions were obtained for the biomass, CO2 and acetate fluxes at the higher dilution rates. The results suggest that fed-batch culture using glycerol as carbon source along with an exponential feed to maintain a 0.1 h-1 specific growth rate as a promising strategy to obtain high cellular concentrations of wild-type S. typhimurium. The efficient acetate uptake observed for the recombinant S. typhimurium cells may allow higher values of specific growth rate to be used for this strain, resulting in a higher productivity of biomass.